Daun Sirih Hutan (Piper Aduncum) Terhadap Penghambatan Transport Glukosa Menggunakan Ileum Tikus Putih (Rattus Novergicus) dengan Metode Infusa - Haryanto Haryanto; Febriyanti Aswinda (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Diabetes mellitus is one of the chronic diseases whose prevalence is increasing worldwide. This disease is characterized by high blood glucose levels due to impaired insulin production or function, the hormone that regulates blood sugar levels. This study aims to examine the effect of wild betel leaf extract (Piper aduncum) on the inhibition of glucose transport using the ileum of white rats (Rattus norvegicus) with the infusion method. This research is a pre-experimental study with a posttest-only control design using white rats and wild betel leaves. The study demonstrates that wild betel leaves (Piper aduncum L.) and red betel leaves (Piper crocatum) have significant potential in inhibiting glucose transport and reducing blood sugar levels. This is evident from the significant decrease in the rate of glucose transport after the administration of wild betel leaf extract, indicating an inhibitory effect on glucose transporters such as SGLT-1 and GLUT-2.